M.B.C. Slade correspondence - Slade, M. B. C.
Letter (1878 April 29) written by Slade to the music publishing firm of Biglow & Main.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Biglow & Main; Music publishers